THE ROLE OF JOB SATISFACTION IN THE WORK ENVIRONMENT ON EMPLOYEE PERFORMANCE - Iskandar, Dani; Sitanggang, Indra Wandi (International Proceeding of Law and Economic; 2020: International Proceeding of Law and Economic, 2021)
The problem of this research is the decline in employee performance, employee performance that is not optimal, the work environment which are less comfortable, such as lighting and some room management that has not been maximized can be seen from the condition of the narrow workspace in the office space, there are often misunderstandings among fellow employees caused by the many work demands (workload) received by these employees are different, thus making employees dissatisfied., of some of the problems that exist withinPDAM Tirtanadi, North Sumatra Province, the author limits the problem of the work environment on employee performance through job satisfaction. The purpose of the study aims to analyze several things, namely: to find out and analyze the influence of the work environment on employee performance, to find out and analyze the influence of the work environment on job satisfaction, to find out and analyze the influence of job satisfaction on employee performance and to determine and analyze the environment work has an effect on performance mediated by job satisfaction at PDAM Tirtanadi, North Sumatra Province. In this study using associative and quantitative research types with samples in this study as many as 72 respondents who are employees of PDAM Tirtanadi, North Sumatra Province.0.327 and0.383, F-Square0.041, 0.645 and 0.174. Mediation effect 0.126, 0.000, 0.000 and0.0013.This shows that: the effect of the work environment on employee performance is positive and not significant; the effect of the work environment on job satisfaction is positive and significant; the effect of job satisfaction on employee performance is positive and significant, the work environment as a mediator variable acts as a mediation on the effect of the work environment on employee performance.